Regulatory effects of berberine on intestinal microecology in mice with ulcerative colitis - Xu, Xinyi; Zhao, Bin; Liu, Pingyu; Tang, Xiaohui; Lai, Zonglang; Song, Na; Cheng, Jun (Frontiers in Microbiology, 2025)
BackgroundCurrently, therapeutic approaches for ulcerative colitis (UC), such as aminosalicylates, glucocorticoids, and biologics, exhibit certain efficacy but are hindered by limitations including side effects, high costs, or suboptimal responses. As a traditional Chinese medicine component, berberine (BBR) possesses anti-inflammatory properties and the ability to modulate the gut microbiota, with low toxicity, and may provide new directions for UC treatment in the future.MethodsA mouse UC model was established via dextran sulfate sodium (DSS) induction, and dose-and time-dependent screening was performed to determine the optimal BBR dosage and intervention duration for subsequent experiments. The disease activity index (DAI) and colon length were measured. Colonic tissue changes were observed via HE staining. Serum cytokine levels (IL-1β, TNF-α, IL-10, TGF-β) were detected using ELISA. The expression levels of ZO-1 and Occludin in mouse colonic tissues were detected by WB. Further analyses included 16S rRNA sequencing to assess gut microbiota diversity and composition, untargeted metabolomics to identify differential metabolites in intestinal tissues, and Mendelian randomization (MR) analysis to explore causal associations among intestinal genes, circulating metabolites, and key bacterial genera. Finally, functional validation was performed by inhibiting the PDGFA receptor.ResultsBerberine significantly alleviated the DAI score, colonic pathological damage, and cytokine imbalance in UC mice, as well as restored mucosal barrier integrity, with the most pronounced effects observed in the UC + low-BBR 14 days group. Gut microbiota analysis revealed distinct microbial structures across groups, with the UC + low-BBR 14 days group showing significantly higher relative abundances of Bacteroides, Alistipes, and unclassified_Clostridia_vadinBB60_group compared to the UC group (p < 0.05). Metabolomics analysis indicated that berberine altered the composition of intestinal tissue metabolites and metabolic pathways. MR analysis demonstrated inverse causal associations between PDGFA and lithocholate sulfate, as well as between lithocholate sulfate and Alistipes. Additionally, inhibition of the PDGFA receptor reversed the therapeutic effects of BBR, exacerbating inflammatory responses and intestinal mucosal barrier damage. Finally, the correlation analysis between gut microbiota and metabolites also confirmed that the abundance of the genus Alistipes exhibited a highly significant negative correlation with lithocholate sulfate levels (p < 0.001).ConclusionBerberine ameliorates symptoms of UC in mice by regulating gut microbiota and metabolite composition. MR analysis first establishes a unidirectional causal chain of PDGFA/lithocholate sulfate/Alistipes, and animal experiments confirm that blocking the PDGFA receptor reverses its therapeutic effects and aggravates inflammation and intestinal mucosal injury.